Pelatihan Penggunaan Educational Game: Kahoot Sebagai Evaluasi Pembelajaran Daring di UPTD SDN Nagrikaler - Wulan Yulianti; Fitri Nuraeni; Sayyida Fakhrun Nisa; Hani Rahmadhani; Evita Nur Aulia; Muhammad Farriz Nur’itsna Adinegoro; Rian Firmansyah; Anwar Mulyana (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2023)
Along with the development of the times and the advancement of human civilization, almost all aspects of human life are influenced by the existence of technology. The education aspect is no exception, where there are currently many uses of various forms of technology-based learning media to facilitate the learning process of teachers to students. One of them is the Kahoot application which offers various features and ease of access for its users. In connection with the advantages of the application, training on the use of the Kahoot application was held for teachers at UPTD SDN 9 Nagrikaler. The method of implementing this training is using a descriptive method. The training was carried out in three stages, namely pre-training, training, and post-training. The results of the Kahoot application training for teachers at UPTD SDN 9 Nagrikaler showed that 100% of the teachers were interested and tried to take part in the Kahoot application training and felt helped afterwards.Along with the development of the times and the advancement of human civilization, almost all aspects of human life are influenced by the existence of technology. The education aspect is no exception, where there are currently many uses of various forms of technology-based learning media to facilitate the learning process of teachers to students. One of them is the Kahoot application which offers various features and ease of access for its users. In connection with the advantages of the application, training on the use of the Kahoot application was held for teachers at UPTD SDN 9 Nagrikaler. The method of implementing this training is using a descriptive method. The training was carried out in three stages, namely pre-training, training, and post-training. The results of the Kahoot application training for teachers at UPTD SDN 9 Nagrikaler showed that 100% of the teachers were interested and tried to take part in the Kahoot application training and felt helped afterwards.